The implementation of lean manufacturing to increase productivity in a textile company: case of study - Rosadio Vela, Jimena Roxana (2022)
Nowadays agile methodologies have been developed, and are used in organizations because companies face highly competitive and globalized markets with constant changes (Arias, 2020). The paper is going to be based on “Lean Manufacturing” which is a system that aims to eliminate waste from the process through continuous and systematic improvement (Palaniswamy, 2021), without generating waste or defective products. The case of the study is based on solving the problem of low productivity for a textile company in Peru, which had been caused by the excessive waiting times between operations and manual activities with a higher percentage of defective products, for example, 7% in the clothing area. In this paper first, we recollected the actual information like batches, the floor plan, production costs, etc. within we simulated the as-is and after that the as-if. This article uses the “Lean Manufacturing” methodology and with it, the losses of products in manual processes will be minimized, going from 10% of safety stock to 6% per order. This goal is going to achieve optimizing transfer times between areas and eliminate those activities that do not generate value for the company, using tools such as “5S”, “Value Stream Mapping”, “Acceptance Control Charts”, “Just In Time”, “Process Reengineering” and “Simulation”. Through simulation with the Arena software, the results were validated, achieving an improvement in the reduction of times by 5.8% and increased productivity by 4.1% thanks to tools such as VSM, line balance, and control charts. The importance of this study is the findings can be replicated in other papers from the textile industry.